2015
DOI: 10.1590/s0102-865020150120000008
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cyclooxygenase-2 activity leads to intestinal dysmotility following hemorrhagic shock

Abstract: PURPOSE:To test whether hemorrhagic shock (HS) increases the Cyclooxygenase-2 (COX-2) expression in the intestine and whether this enhanced COX-2 expression mediates the intestinal dysmotility after HS. METHODS: Male Wistar rats were randomly divided into HS sham group and HS group. At 180 min following HS establishment, the duodenum samples were harvested to assess the motility function, protein expression of COX-2 and the downstream products of COX-2, prostaglandins . RESULTS: Examination of motility functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Yu-Ping Zhang et al . previously observed a high level of COX-2 at the site of hemorrhagic injury35. Other research groups demonstrated that the inhibition of COX-2 expression and PGE 2 production could alleviate hemorrhagic gastrointestinal36, brain37, and bladder-related injury to improve survival in vivo 38.…”
Section: Discussionmentioning
confidence: 94%
“…Yu-Ping Zhang et al . previously observed a high level of COX-2 at the site of hemorrhagic injury35. Other research groups demonstrated that the inhibition of COX-2 expression and PGE 2 production could alleviate hemorrhagic gastrointestinal36, brain37, and bladder-related injury to improve survival in vivo 38.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies have also suggested that both COX-1 and COX-2 are important in the formation of collagen during wound healing, and that their deficiency may lead to alterations in the development of granulation tissue and re-epithelialization by inhibiting the proliferation of keratinocytes 12,19,20,23 .…”
mentioning
confidence: 99%